2014
DOI: 10.1073/pnas.1403477111
|View full text |Cite
|
Sign up to set email alerts
|

Caspase-8 and RIP kinases regulate bacteria-induced innate immune responses and cell death

Abstract: A number of pathogens cause host cell death upon infection, and Yersinia pestis, infamous for its role in large pandemics such as the "Black Death" in medieval Europe, induces considerable cytotoxicity. The rapid killing of macrophages induced by Y. pestis, dependent upon type III secretion system effector Yersinia outer protein J (YopJ), is minimally affected by the absence of caspase-1, caspase-11, Fas ligand, and TNF. Caspase-8 is known to mediate apoptotic death in response to infection with several viruse… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

15
263
3
3

Year Published

2014
2014
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 263 publications
(295 citation statements)
references
References 49 publications
(51 reference statements)
15
263
3
3
Order By: Relevance
“…Myeloid cells can undergo necroptosis in response to a variety of pathogenic signals. 27,40 Hence, future studies must address the possible contribution of chemotherapy-induced necroptosis in inflammatory and immune cells in anticancer immunosurveillance. Irrespective of this limitation, the present data support the notion that RIP3 and MLKL may participate to chemotherapy-induced ICD.…”
Section: Discussionmentioning
confidence: 99%
“…Myeloid cells can undergo necroptosis in response to a variety of pathogenic signals. 27,40 Hence, future studies must address the possible contribution of chemotherapy-induced necroptosis in inflammatory and immune cells in anticancer immunosurveillance. Irrespective of this limitation, the present data support the notion that RIP3 and MLKL may participate to chemotherapy-induced ICD.…”
Section: Discussionmentioning
confidence: 99%
“…However, the role of caspase 8 is complex and context dependent as the causative agent of plague Yersinia pestis and its outer protein YopJ employs caspase 8, RIP1 and RIP3 to trigger cell death and caspase 1 activation. 123,124 Interestingly, another study demonstrated that pharmacological or genetic depletion of the cIAP proteins in macrophages, in conjunction with TLR stimulation, resulted in augmented processing of pro-IL-1b into its mature form. 125 The processing of IL-1b was driven by two independent pathways involving NLRP3/caspase 1 and caspase 8.…”
Section: Rip Kinases and The Inflammasomementioning
confidence: 99%
“…It cannot be excluded that other intra-and extrahepatic cell compartments than hepatocytes-such as monocytes or T cells-are targeted by repetitive injections of antisense oligonucleotides. (3) Of note, macrophages lacking Ripk1 show reduced cytokine production, impaired nuclear factor kappa B activation, and greatly compromised caspase 1 processing, (4) which might contribute to the beneficial effects upon oligomer injections. (2) This would also explain the similarity between the findings from Dara et al and previous results using the chemical inhibitor Nec-1 in the acetaminophen model.…”
Section: Lpc-komentioning
confidence: 99%